Stage-specific associations of mineralization markers with CKM syndrome: Nationwide survey and genetic evidence for Alkaline phosphatase’s unique clinical role - Lei Hua; Yongshou Tao; Liangru Shen (PLoS ONE, 2026)
Background Cardiovascular-Kidney-Metabolic (CKM) syndrome involves disordered mineralization processes. Herein, we investigated the serum alkaline phosphatase (ALP), calcium, and phosphorus across CKM stages. Methods This study analyzed 15,233 eligible participants in National Health and Nutrition Examination Survey (2009–2018) using survey-weighted multinomial logistic regression to assess associations of ALP, calcium, and phosphorus. Restricted cubic splines assessed non-linear relationships, while Cox models examined mortality risks. Two-sample Mendelian randomization (MR) explored causal relationships. Results Relative risk ratios (RRRs) and 95% confidence intervals (95% CI) were calculated with multinomial logistic regression. Compared with stage 0, ALP was positively associated with the likelihood of being classified into stage 2 (RRR, 1.23[95% CI, 1.11–1.37]), stage 3 (RRR, 1.99 [95% CI, 1.48–2.67]), stage 4a (RRR, 1.29 [95% CI, 1.14–1.46]), stage 4b (RRR, 1.35 [95% CI, 1.16–1.58]). Per mg/dL increase in serum calcium levels was associated with a higher likelihood of being classified into stages 2 (RRR = 2.13, 95% CI: 1.55–2.94) and CKM stage 4, while per mg/dL increase in serum phosphorus was associated with stage 3 classification (RRR = 2.85, 95% CI: 1.77–4.59) and the results remained consistent after standardizing the markers using z-scores. ALP’s 4th quartile was associated with the highest mortality risks (CKM-cause hazard ratio = 2.20; all-cause hazard ratio = 2.15). MR analysis indicated potential causal effects of ALP on cardiovascular disease and of chronic kidney disease on ALP. Conclusions ALP demonstrates consistent associations with all CKM stages. These findings indicate that ALP-related mechanisms need further exploration.